Analisis risiko imbal hasil dan risiko investasi dalam perbankan syariah - Aqilah, Naurah Nadhifah (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze rate of return risk and investment risk as two distinctive risks in Islamic banking that affect performance stability and customer trust. The research employed a descriptive qualitative approach through a literature study by reviewing various scholarly sources related to risk management in Islamic banking. The findings indicate that rate of return risk arises when the profit-sharing returns offered by Islamic banks are unable to compete with returns provided by other financial institutions, potentially encouraging customers to transfer their funds. Meanwhile, investment risk emerges from the bank’s involvement in profit-sharing financing contracts such as mudharabah and musyarakah, where the bank shares losses if the financed business fails. These two risks have different characteristics but are closely interrelated. An increase in investment risk may reduce bank income and consequently weaken the bank’s ability to offer competitive returns. This condition highlights the importance of an integrated risk management system. Mitigation efforts include improving financing feasibility analysis, diversifying financing portfolios, and establishing competitive profit-sharing strategies in accordance with sharia principles. Through proper risk management, Islamic banks can maintain business sustainability, enhance competitiveness, and preserve customer trust.